Internet Financial Reporting in Bosnia and Herzegovina - Tarik Zaimovic; Azra Zaimovic; Anela Fazlic (Economic Review: Journal of Economics and Business, 2015)
Using the Internet as a communication channel between a company and its stakeholders is a norm in today's economy, and the Web- based company reports have long replaced traditional forms of corporate reporting. Most investors base their entire first impression of a company on information available on its Web page, and often, an entire initial performance assessment is based on data available on-line. Internet Financial Reporting (IFR), in its broadest form, has become one of the pivotal factors in effective functioning of capital markets. Building on earlier studies, we analyzed the IFR practices of companies traded on two stock exchanges in Bosnia and Herzegovina by estimating multiple regressions separately for both stock exchanges. Our findings clearly show that voluntary disclosure of reports and other forms of company information for analyzed companies is still simplistic. Furthermore, our estimations revealed that profitability measured by return on equity and market activity represented by share turnover significantly affect the IFR index for companies traded on the Banja Luka Stock Exchange (BLSE); with companies traded on the Sarajevo Stock Exchange (SASE), size measured by total asset, as well as market activity measured by share turnover, have a positive effect on the IFR index. On both stock exchanges, companies from the financial industry have on average higher IFR scores than other companies. With respect to expanding earlier studies, this study used an extended sample for Bosnian and Herzegovinian assessments, and as a result, observed additional factors related to the Internet Financial Reporting practices of companies traded on two stock markets in B&H.
Keywords: G32; 330; The Internet financial reporting; SASE; BLSE; B&H